И.ЮСУПОВ ПОЭЗИЯСЫНДА СОМАТИКАЛЫҚ ФРАЗЕОЛОГИЗМЛЕРДИҢ СТИЛЬЛИК ҚОЛЛАНЫЎЫ - Алламбергенова, Г. (SCIENCE and SOCIETY, 2018)
Phraseological units in the Karakalpak language are often used in everyday speech and also in the texts of the belles – letters style. There are phraseologisms in the Karakalpak language belonging to the names of human body (somatisms). On the basis of examples the author of the article studies the peculiarities of using phraseologisms-somatisms in the work of famous Karakalpak poet I.Yusupov.